Human lymphocytes interact directly with CD47 through a novel member of the signal regulatory protein (SIRP) family - Brooke, G; Holbrook, J; Brown, M; Barclay, A (2004)
Two closely related proteins, signal regulatory protein α (SIRPα; SHPS-1/CD172) and SIRPβ, have been described in humans. The existence of a third SIRP protein has been suggested by cDNA sequence only. We show that this third SIRP is a separate gene that is expressed as a protein with unique characteristics from both α and β genes and suggest that this gene should be termed SIRPγ. We have expressed the extracellular region of SIRPγ as a soluble protein and have shown that, like SIRPα, it binds CD47, but with a lower affinity (Kd, ∼23 μM) compared with SIRPα (Kd, ∼2 μM). mAbs specific to SIRPγ show that it was not expressed on myeloid cells, in contrast to SIRPα and -β, being expressed instead on the majority of T cells and a proportion of B cells. The short cytoplasmic tail of SIRPγ does not contain any known signaling motifs, nor does it contain a characteristic lysine, as with SIRPα, that is required for DAP12 interaction. DAP12 coexpression is a requirement for SIRPβ surface expression, whereas SIRPγ is expressed in its absence. The SIRPγ-CD47 interaction may therefore not be capable of bidirectional signaling as with the SIRPα-CD47, but, instead, use unidirectional signaling via CD47 only.